Analisis Kemampuan Berpikir Kritis Siswa SMA Kelas X IPA dalam Memecahkan Soal Cerita ditinjau dari Gender dan Kemampuan Matematika - Benyamin, Benyamin; Qohar, Abd.; Sulandra, I made (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
The purpose of this study was to describe the critical thinking skills of class X high school students in solving story problems in terms of gender and math abilities. This research was conducted in the even semester of 2020/2021. This research uses a qualitative approach with descriptive research type. The subjects in this study consisted of 3 male students and 3 female students with different mathematical abilities selected based on test results and consultation with subject teachers. The used Instruments in this study were critical thinking skills tests and interviews. The results of this research are (1) male students and high mathematical abilities meet aspects of interpretation, analysis, evaluation, inference, aspects and self regulation well. Meanwhile, female students with high mathematical abilities are able to complete aspects of interpretation, analysis, evaluation, and inference well; (2) Male students and their mathematical abilities are meeting the aspects of interpretation, analysis, and inference well. Meanwhile, female students and moderate math abilities were able to complete interpretation, analysis, inference, and explanation well; and (3) male students with low math ability are able to solve aspects of interpretation well. Meanwhile, female students with low math abilities were able to complete aspects of interpretation and analysis well. For further researchers, it is necessary to research at a higher level with more research subjects or on other variables.